Perilaku dan Sikap Karakteristik serta Ekonomi Masyarakat Pesisir di Dusun XIV Desa Percut - Fitria, Adinda Dwi; Sianturi, Anggina Cucu Khetri; Salwa, Fadillah; Haridani, Hifza; Manik, Hubban Fathani; Khairini, Khovifah; Dasopang, Lailatul Mahpuja; Lestari, Ninis; Rahmawati, Nurul; Sagala, Shinny Syafitri; Arika, Romiza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Coastal communities are those who live and dwell in coastal areas, which are transitional areas marking the transition between land and sea. Most coastal communities live by managing coastal and marine resources, either directly or indirectly. Coastal communities have a strong, tough, and open social characteristic. They live as fishermen who depend on freely accessible resources, namely the sea. Dependence on the sea as the main resource for catching fish is influenced by irregular and high-risk climate.